Gasification improvement of a poor quality solid recovered fuel (SRF): Effect of using natural minerals and biomass wastes blends - Pinto, Filomena (2014)
The need to produce energy from poor quality carbonaceous materials has increased, in order to reduce European dependency on imported fuels, diversify the use of new and alternative fuels and to guarantee secure energy production routes. The valorisation of a poor quality solid residual fuel (SRF), with high content of ash and volatile matter, through its conversion into fuel gas was studied. The rise of gasification temperature and equivalent ratio (ER) led to higher gas yields and to lower undesirable gaseous components, though higher ER values led to a gas with lower energetic content. To reduce the negative effect of SRF unfavourable characteristics and to diversify the feedstocks used, SRF blended with three different types of biomass wastes: forestry pine, almond shells and olive bagasse was co-gasified. The use of biomass wastes tested was valuable for SRF gasification, as there was an increase in the overall reactivity and in H2 production and a reduction of about 55% in tar released, without great changes in gas yield and in its HHV. The use of natural minerals mixed with silica sand was also studied with the aim of improving SRF gasification performance and fuel gas quality. The best results were obtained in presence of dolomite, as the lowest tar and H2S contents were obtained, while an increase in gas yield was observed. Co-gasification of this poor quality SRF blended with biomass wastes in presence of dolomite increased gas yield by 25% while tar contents decreased by 55%.